Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Kognitif Tentang Biologi Siswa Berkemampuan Akademik Tinggi Dan Berkemampuan Akademik Rendah Kelas XI Di SMA Negeri 1 Palu - Lita Iriani; Hartono D. Mamu; Lilies N. Tangge (Mitra Sains, 2015)
The research aimed at investigating the effect of model of cooperative learning Type jigsaw, academic ability of student, and interaction between learning model with the level of academic ability, on the cognitive learning outcomes of student. The method used is quasi-experimental pretest-posttest 2 x 2 factorial pattern. The research sample is determined with random sampling. The class selected as the research sample was class XI IPA 1, XI IPA 3, XI IPA 6, and XI IPA 7. The data was collected by using the cognitive achievement test typical the multiple choice Data obtained was the primary data, which directly analyzed descriptively and analysis of covariance. Results of the data analysis at significance level α = 0.05 is as follow: (1) the cognitive learning outcomes of student that were learned by the model of cooperative learning type jigsaw (mean = 82.22) was higher than the cognitive learning outcomes of student that were learned with the conventional learning (mean = 73.56) with a significance value of 0.000. (2) The cognitive learning outcomes of student who have the high level academic ability (mean = 85.10) was higher than the cognitive learning outcomes of student who have lower level of academic ability (mean = 72.36) with a significance value of 0.000. (3) There is an interaction effect between the model of cooperative learning with the academic abilitywith the significance value of 0.002 was obtained in this case. Based on the results of this research, it can be concluded that: The model of cooperative learning type jigsaw, the academic ability, and the interaction between the model of cooperative learning with the academic ability effect on the cognitive learning outcomes.